Inverse association between pre-high-altitude potassium levels and coronary microvascular disease at high altitude: a case-control study - Chen, Yu; Ren, Yong; Zhang, Xin; Zhou, Wen-Bao; Zhang, Wen-Tao; Lv, Juan; Rao, Xi-Yang; Zi, Rui-Xi; Wang, Si-Jie; Wang, Li-Sha; Bao, Chun-Ping; Yang, Li-Xia; et al. (Frontiers in Pharmacology, 2025)
Background and ObjectivesHigh-altitude hypoxia is known to impair cardiac microvascular function, a pathophysiological state recognized as coronary microvascular disease (CMVD). This study aimed to investigate the independent association between serum potassium levels and the risk of developing CMVD, after controlling for traditional cardiovascular risk factors such as hypertension, dyslipidemia, and smoking.MethodsThis case-control study enrolled 1,175 trainees with long-term exposure to high altitude (≥3,000 m), comprising 235 patients with CMVD (cases) and 940 healthy controls. We employed multivariable logistic regression analysis to systematically evaluate the associations of traditional risk factors and serum potassium levels with the risk of CMVD.ResultsA key finding from our analysis was a significant inverse association between serum potassium levels and the odds of CMVD (OR = 0.26; 95% CI, 0.14–0.47). Specifically, higher potassium concentrations were correlated with a substantially lower disease risk. This inverse association was more prominent in individuals with a moderate body mass index and in smokers.ConclusionThis is the first study to demonstrate that a higher serum potassium level is independently associated with lower odds of CMVD in populations exposed to high altitudes. This finding provides a new direction for developing targeted health screening and preventive strategies in high-altitude regions, holding significant potential for protecting specific at-risk groups such as individuals with a particular BMI, and smokers.